Mu'awiyah Bin Abu Sufyan's Tactics In Beating Ali Bin Abi Thalib - Arfah Ibrahim (SHIBGHAH: Journal of Muslim Societies, 2020)
This study aims to determine the strategy of Mua'wiyah bin Abu Sufyan in the formation of the majlis tahkim so that he gets a victory and to know the course of the trial of tahkim between Ali and Mua'wiyah. This type of research is qualitative research with a historical approach. These sources the author obtained by using data collection techniques, namely through the research library. The results of this study indicate that during the war Siffin had appeared to be won by the Caliph Ali bin Abi Talib, Mu'awiyah carried out war tactics by raising the Koran to ask for peace according to Al-Quran instructions so that the war was stopped so that the war was forced to stop. Many factors caused Mu'awiyah to win. Among them, he attracted people who influenced his side to strengthen the ranks, and he spent a lot of state money to give to his followers so they could unite in usurping power from the hands of the caliph Ali bin Abi Talib.